IMPLEMENTASI MODERASI BERAGAMA DALAM MENINGKATKAN KESADARAN HUKUM MASYARAKAT TERHADAP PENCEGAHAN PAHAM RADIKALISME - Made Widhiyana (Belom Bahadat, 2022)
Religious moderation is one way to maintain the unity and integrity of the Unitary State of the Republic of Indonesia (NKRI) from a socio-religious perspective. The harmony of social and religious life can be seen from how far the values ​​of religious moderation apply. Religious moderation becomes a magnet that can attract various religious adherents, that all are in the same environment and a sense of unity that will be able to maintain security and peace in the life of the nation and society. By implementing religious moderation as well as an indication of compliance or legal awareness of the community in participating in maintaining harmony. Because without legal compliance and awareness embedded in each individual, bad influences will easily influence him, call it radicalism. For those who are led in the notion of radicalism, it will be easy to carry out radical actions that ultimately lead to terrorism. The emergence of radical actions will certainly lead to division, far from the words tolerance and harmony. Meanwhile, the Indonesian people are wrapped in a frame of diversity that must be maintained and maintained as one of the characteristics of this nation. So it is important to implement the values ​​of religious moderation to increase public legal awareness in order to prevent entering the circle of radicalism.